Reflections I and II: Reflections from Education and the Arts in the COVID-19 Era - McLaren, Peter; Yan, Wang; Jandrić, Petar (Communiars. Revista de Imagen, Artes y Educación Crítica y Social, 2020)
Reflection I comes from the North American context, from Chapman University (USA). Peter McLaren is a professor at Chapman University, a researcher of reference in the international field of critical pedagogy. Wang Yan is a researcher in the Faculty of Educational Studies at Chapman University, her current research interest include Culture and Curricular Studies. Reflection II is developed by Petar Jandrić, professor at University of Applied Sciences of Zagreb (Croatia), researcher and expertise in understanding the intersections between critical pedagogy and information and communication technologies.